Harnessing practitioner knowledge to inform the conservation of a protected species, the hazel dormouse Muscardinus avellanarius. Issue 4 (4th December 2022) - Phillips, Benjamin B.; Crowley, Sarah L.; Bell, Olivia; McDonald, Robbie A.
Abstract: Conservation decisions are typically constrained by the availability of published evidence. Practitioners and non‐academic experts often possess additional knowledge, including about the practical plausibility of conservation actions, which may lead to more effective planning and outcomes. However, practitioner knowledge is rarely considered during formal evidence syntheses. Alongside a formal literature review, we conducted 26 interviews involving 38 conservation professionals to elicit their knowledge of the conservation of a protected and declining species in England, the hazel dormouse Muscardinus avellanarius . Practitioners and non‐academic experts provided additional insights about dormouse ecology and conservation, beyond those synthesized from the published literature, though we found few contradictions between these different information sources. Instead, practitioner knowledge helped to verify, clarify and expand upon evidence from empirical studies. In general, practitioners emphasized that dormice are far more adaptable than traditionally perceived, with thriving populations found in hedgerows, scrub, road verges and railway verges, rather than solely within broadleaf woodlands. Proposed opportunities for restoring dormouse populations included improving hedgerow management, creating new woodlands, bringing existing woodlands back into management, setting aside unproductive land and improving habitat connectivity. However, participants emphasized the need for landscape‐scale approaches, accounting for the impacts of climate change, and better surveying and monitoring. Key practical considerations included overcoming time and financial constraints, providing better advice, knowledge and training, changing attitudes of land owners and managers and balancing other demands such as agricultural productivity and the requirements of other species. Despite the insights they provided, participants highlighted many remaining knowledge gaps. These included uncertainties arising from the published literature, as well as scarcely studied topics that are of major practical importance, namely the effectiveness of dormouse mitigation measures in planning and development, and the impacts of anthropogenic disturbance and pollution on dormice. Our findings improve the evidence base for restoring hazel dormouse populations and for further empirical evidence gathering. More generally, the study highlights how practitioner knowledge can help both to supplement traditional published evidence and to better frame conservation programmes, which may lead to more successful outcomes. Abstract : We gathered and analysed practitioner knowledge, with a view to informing the conservation of a protected species in England, the hazel dormouse. Practitioners and non‐academic experts provided additional insights about dormouse ecology and conservation that helped to verify, clarify and expand upon evidence from empirical studies. Image by Björn Schulz (https://commons.wikimedia.org/wiki/File:Haselmaus.JPG ).